Min al-Ḥarbi ḷla al-ḷṣlaḥ wa al-Salam: Tafsiru Āyāti āl-Ǧihād ʿala Ḍawʾi Maqaṣidihā - Hasbillah, Ahmad Ubaydi (UIN Sunan Kalijaga Yogyakarta, 2022)
The interpretation of jihadi verses has been still within the framework of the vision of